Diarrhea-Causing Bacteria and Their Antibiotic Resistance Patterns Among Diarrhea Patients From Ghana - Afum, Theophilus; Asandem, Diana Asema; Asare, Prince; Asante-Poku, Adwoa; Mensah, Gloria Ivy; Musah, Abdul Basit; Opare, David; Taniguchi, Kiyosi; Guinko, Nuhu Muniru; Aphour, Thelma; Arhin, Doris; Ishikawa, Koichi; et al. (Frontiers in Microbiology, 2022)
Diarrheal disease remains a major global health problem particularly in children under five years and the emergence of antibiotic-resistant strains of causative pathogens could slow control efforts, particularly in settings where treatment options are limited. This surveillance study conducted in Ghana aimed to determine the prevalence and antimicrobial susceptibility profile of diarrhea-causing bacteria. This was a cross-sectional study carried out in five health facilities in the Ga West Municipality of Ghana between 2017-2021. Diarrheic stool samples from patients were collected and cultured on standard differential/selective media and isolates identified by, standard biochemical tests, MALDI-TOF assay, and serological analysis. The antibiogram was determined using Kirby-Bauer disk diffusion and Microscan autoScan4 MIC panels which were used for ESBL detection. Results: Bacteria were isolated from 97.5% (772/792) of stool samples, and 167 of the isolates were diarrheagenic and met our inclusion criteria for antimicrobial resistance (AMR) analysis. This included Escherichia coli (49.1%, (82/167), Salmonella species (23.9%, (40/167), Vibrio species (16.8%, (28/167), and Shigella species (10.2%, (17/167). Among 24 Vibrio species successfully tested for AMR, we observed resistances to cefotaxime (21/24, 87.5%), ceftriaxone (20/24, 83.3%), and ciprofloxacin (6/24, 25%), including four multi-drug resistant isolates. All 13 Vibrio parahaemolyticus isolates were resistant to cefazolin. All 17 Shigella isolates were resistant to tetracycline with resistances to shigellosis drugs such as norfloxacin and ciprofloxacin. Salmonella isolates were highly susceptible to norfloxacin (40/40, 100%) and tetracycline (12/34, 35%). Two eExtended-sSpectrum beta-lactamase-producing (ESBL) E. coli were also identified with marked susceptibility to gentamicin (66/72, 91.7%) and amikacin (57/72, 79.2%) prescribed in the treatment of E. coli infections. This study showed the different bacteria implicated in diarrhea cases in Ghana and the need for differential diagnoses for better treatment outcomes. E. coli, Shigella, Salmonella and Vibrio have all been implicated in diarrhea cases in Ghana. The highest prevalence was E. coli and Salmonella with Shigella the least prevalent. Resistance to commonly used drugs these isolates may render bacteria infection treatment in the near future nearly impossible. Routine antimicrobial susceptibility testing, effective monitoring, and nationwide surveillance of AMR pathogens should be implemented to curb the increase of antimicrobial resistance in Ghana.